Influência do manejo pré-abate na qualidade da carne de suínos - Jacinto, Jessika Soares (2017)
The objective of this work was to evaluate the quality of the final product related to the pre-slaughtering of pigs, which allowed the analysis of procedures and compliance with animal welfare standards. Pre-slaughter management is defined as the set of practices with the animals from the property to the slaughterhouse. Pre- slaughter procedures are directly related to losses related to meat quality and economic losses throughout the production system. A total of 144 animals were evaluated over a six day slaughter period in relation to water retention capacity, initial and final pH, and staining. Subsequently, the results were analyzed with regard to technological defects such as PSE and DFD. It was concluded that improper handling influenced the quality of the products.